Super-hydrophobic anti-reflection self-cleaning coating material and preparation method thereof

By using components such as silicon-based mesoporous materials, nanotitanium dioxide and nanographene in superhydrophobic coatings, forming a coating with self-cleaning and high transmissivity, the problem of short service time of the existing coating is solved, and the problem of achieving the Effective removal of various pollutants and improve durability.

CN119242088AActive Publication Date: 2025-01-03CHONGQING UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410291963.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2025-01-03
Estimated Expiration
2044-03-14

AI Technical Summary

Technical Problem

In actual use, the existing superhydrophobic coatings have too short service time due to the accumulation of pollutants, and it is impossible to effectively remove pollutants of various characteristics.

Method used

Using silicon-based mesoporous material as a carrier, the active group of cocolic acid diethanolamide is introduced and nanotitanium dioxide is installed, combined with nanographene and expanded graphite, and the velvet structure is formed through ultrasonic dispersion and stirring. The pollutants are washed away by rainwater and through Surfactants modify expanded graphite to improve antistatic properties.

Benefits of technology

It significantly improves the stain resistance and permeability of the coating, extends service time, reduces replacement costs, and achieves effective removal of various pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242088A_ABST
    Figure CN119242088A_ABST
Patent Text Reader

Abstract

The invention discloses a super-hydrophobic anti-reflection type self-cleaning coating material and a preparation method thereof. The super-hydrophobic self-cleaning coating material is prepared from 1 to 3 parts of a silicon-based mesoporous material, 4 to 5 parts of coco fatty acid diethanol amide, 1 to 3 parts of nano titanium dioxide, 3 to 5 parts of dodecyl methacrylate, 1 to 3 parts of a polyethylene glycol type antistatic agent, 1 to 3 parts of expanded graphite, 1 to 3 parts of nano graphene, 30 to 50 parts of absolute ethyl alcohol and 20 to 30 parts of acetone. In the invention, through the synergistic effect of the components, the formed coating has better hydrophobicity, durability, stain resistance, anti-reflection property and antistatic property, so that the self-cleaning effect of the coating is good, the service time of the coating is greatly prolonged, and the frequent replacement cost of the coating is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of self-cleaning materials, and in particular relates to a super-hydrophobic anti-reflective self-cleaning coating material and a preparation method thereof. Background Art

[0002] As one of the clean, efficient and inexhaustible green energy technologies of the future, solar energy technology has been increasingly widely used in recent years. The solar photovoltaic glass industry, a product that combines solar energy utilization with the traditional glass industry, is becoming one of the fastest growing high-tech industries in the world and is known as an emerging sunrise industry. In recent years, the photovoltaic power generation industry has developed rapidly, and the installed capacity has experienced explosive growth. Due to the influence of national policies that encourage the development of distributed photovoltaic power generation, distributed photovoltaic power generation has also developed rapidly. In particular, it is encouraged and advocated to use the roofs of residential buildings and factory buildings to install distributed grid-connected photovoltaic power generation modes.

[0003] However, in recent years, self-cleaning coatings have received widespread attention. Super-hydrophobic (water contact angle> 150 °) self-cleaning coatings, by rolling water droplets to take away dust, achieve a self-cleaning function similar to lotus leaves. However, there are various pollutants in the actual air environment, including both hydrophilic dust pollutants and lipophilic organic pollutants, both solid pollutants and liquid pollutants, as well as a mixture of various pollutants. Existing super-hydrophobic coatings cannot effectively remove pollutants of all different characteristics, resulting in the loss of super-hydrophobic properties of the coating surface due to the continuous accumulation of pollutants during actual use. Therefore, the existing super-hydrophobic coatings still have the problem of short actual service time. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a super hydrophobic anti-reflective self-cleaning coating material and a preparation method thereof, aiming to provide a self-cleaning coating material with a longer service time to solve the technical problem that the current self-cleaning coating has a short service time.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides the following technical solution: a super-hydrophobic anti-reflective self-cleaning coating material, comprising, by weight:

[0007] 1-3 parts of silicon-based mesoporous material;

[0008] Coconut oil diethanolamide 4-5 parts;

[0009] 1-3 parts of nano titanium dioxide;

[0010] 3-5 parts of lauryl methacrylate;

[0011] 1-3 parts of polyethylene glycol type antistatic agent;

[0012] 1-3 parts of expanded graphite;

[0013] 1-3 parts of nanographene;

[0014] 30-50 parts of anhydrous ethanol;

[0015] 20-30 parts of acetone.

[0016] Furthermore, the silicon-based mesoporous material is any one or more of MCM-22, MCM-41, MCM-48 and SBA-15.

[0017] Furthermore, the nano titanium dioxide is an anatase phase crystal with photocatalytic function and a particle size of 2-3 nanometers.

[0018] Further, the composition comprises, by weight:

[0019] 1 part of silicon-based mesoporous material;

[0020] 1 part of nano titanium dioxide;

[0021] Coconut oil diethanolamide 1-2 parts;

[0022] 1-2 parts of methacrylic acid;

[0023] 1-2 parts of methacryloxytrimethylsilane;

[0024] 1-3 parts of lauryl methacrylate;

[0025] 1-3 parts of polyethylene glycol type antistatic agent;

[0026] 1-3 parts of expanded graphite;

[0027] 1-3 parts of nanographene;

[0028] 30-50 parts of anhydrous ethanol;

[0029] 20-30 parts of acetone.

[0030] The present application also discloses a method for preparing a super-hydrophobic anti-reflective self-cleaning coating material, comprising using any of the above-mentioned super-hydrophobic self-cleaning coatings for photovoltaic solar energy, wherein the preparation method comprises the following steps:

[0031] S01: ultrasonically dispersing the silicon-based mesoporous material, nano-titanium dioxide, and coconut oil diethanolamide in silent ethanol, and stirring at a certain temperature to form a first mixture;

[0032] S02: adding anhydrous ethanol, polyethylene glycol type antistatic agent and expanded graphite to the first mixture and stirring evenly to form a second mixture;

[0033] S03: adding dodecanol methacrylate, nanographene and acetone to the second mixture and stirring for 30-45 minutes, mixing evenly, filtering and drying to form a self-cleaning coating material.

[0034] Furthermore, the stirring time in step S01 is 30-45 minutes, and the stirring temperature is 80-100°C.

[0035] Furthermore, the step S03 further includes:

[0036] mixing dodecanol methacrylate, nanographene, acetone, methacryloxytrimethylsilane, and methacrylic acid to form an intermediate product;

[0037] The second mixture and the intermediate product are stirred, mixed evenly, filtered and dried to form a self-cleaning coating material.

[0038] Furthermore, the step S01 further includes:

[0039] The silicon-based mesoporous material is surface treated with fluorination to introduce active reaction sites.

[0040] Furthermore, the step S01 further includes:

[0041] The silicon-based mesoporous material with fluorinated surface treatment is placed in a polyamine acetonitrile solution for reaction for 2-3 hours.

[0042] The beneficial effects of the present invention are as follows: compared with the prior art, the preparation method of a photovoltaic dustproof self-cleaning coating in the present invention uses a silicon-based mesoporous material as a carrier, introduces coconut oil diethanolamide active groups, and carries nano titanium dioxide, so that various organic pollutants can be oxidized and decomposed, and various pollutants are washed by rainwater, thereby removing pollutants accumulated on the surface of the photovoltaic glass plate, so that the film has a self-cleaning effect; the stain resistance of the coating is improved;

[0043] By adding nanographene, a fuzzy structure can be formed on the surface of the coating, which can reduce the reflection of the coating, increase the thermal conductivity of the coating, accelerate the decomposition of organic matter and self-cleaning function, and is conducive to absorbing light from all directions and refracting it onto the photovoltaic module. Especially in a weak light environment, it is more conducive to absorbing scattered light, making the effective transmittance of sunlight greater than 90%, thereby improving the anti-transmittance of the coating;

[0044] By mixing the surfactant-type antistatic agent with the expanded graphite, the surface of the expanded graphite is modified. The modified expanded graphite is not easy to agglomerate, and the expanded graphite can be evenly dispersed in the silicon-based mesopores and will not gradually seep out of the coating during use. As a result, the formed coating has permanent antistatic properties, which prolongs the service life of the coating and reduces the cost of frequent replacement of the coating.

[0045] In the present application, through the synergistic effect of the above-mentioned components, the coating formed has good hydrophobicity, durability, stain resistance, anti-permeability and antistatic properties, so that the coating has a good self-cleaning effect, greatly improves the service life of the coating, and reduces the cost of frequent replacement of the coating.

[0046] Other advantages, objectives and features of the present invention will be described in the following description and will be apparent to those skilled in the art to some extent, or those skilled in the art may be taught from the practice of the present invention. The objectives and other advantages of the present invention may be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:

[0048] Figure 1 A flow chart of a method for preparing a photovoltaic dustproof self-cleaning coating according to an embodiment of the present invention;

[0049] Figure 2 A flowchart of step S03 is provided for one embodiment of the present invention. DETAILED DESCRIPTION

[0050] Embodiment 1

[0051] This embodiment provides a super-hydrophobic anti-reflective self-cleaning coating material, which includes, by weight:

[0052] 1 part of silicon-based mesoporous material; 4 parts of coconut oil diethanolamide; 1 part of nano titanium dioxide; 3 parts of dodecanol methacrylate; 1 part of polyethylene glycol type antistatic agent; 1 part of expanded graphite; 1 part of nano graphene; 30 parts of anhydrous ethanol; and 20 parts of acetone.

[0053] Embodiment 2

[0054] This embodiment provides a super-hydrophobic anti-reflective self-cleaning coating material, which includes, by weight:

[0055] 2 parts of silicon-based mesoporous material; 4.5 parts of coconut oil diethanolamide; 2 parts of nano titanium dioxide; 3 parts of dodecanol methacrylate; 1 part of polyethylene glycol type antistatic agent; 1 part of expanded graphite; 1 part of nano graphene; 30 parts of anhydrous ethanol; and 20 parts of acetone.

[0056] Embodiment 3

[0057] This embodiment provides a super-hydrophobic anti-reflective self-cleaning coating material, which includes, by weight:

[0058] 2 parts of silicon-based mesoporous material; 4.5 parts of coconut oil diethanolamide; 2 parts of nano titanium dioxide; 3 parts of dodecanol methacrylate; 2 parts of polyethylene glycol type antistatic agent; 2 parts of expanded graphite; 1 part of nano graphene; 30 parts of anhydrous ethanol; and 20 parts of acetone.

[0059] Embodiment 4

[0060] This embodiment provides a super-hydrophobic anti-reflective self-cleaning coating material, which includes, by weight:

[0061] 3 parts of silicon-based mesoporous material; 5 parts of coconut oil diethanolamide; 3 parts of nano titanium dioxide; 3 parts of dodecanol methacrylate; 2 parts of polyethylene glycol type antistatic agent; 2 parts of expanded graphite; 1 part of nano graphene; 30 parts of anhydrous ethanol; and 20 parts of acetone.

[0062] Embodiment 5

[0063] This embodiment provides a super-hydrophobic anti-reflective self-cleaning coating material, which includes, by weight:

[0064] 3 parts of silicon-based mesoporous material; 5 parts of coconut oil diethanolamide; 3 parts of nano titanium dioxide; 3 parts of dodecanol methacrylate; 3 parts of polyethylene glycol type antistatic agent; 3 parts of expanded graphite; 1 part of nano graphene; 30 parts of anhydrous ethanol; and 20 parts of acetone.

[0065] Embodiment 6

[0066] This embodiment provides a super-hydrophobic anti-reflective self-cleaning coating material, which includes, by weight:

[0067] 3 parts of silicon-based mesoporous material; 5 parts of coconut oil diethanolamide; 3 parts of nano titanium dioxide; 3 parts of dodecanol methacrylate; 3 parts of polyethylene glycol type antistatic agent; 3 parts of expanded graphite; 2 parts of nano graphene; 30 parts of anhydrous ethanol; and 20 parts of acetone.

[0068] Embodiment 7

[0069] This embodiment provides a super-hydrophobic anti-reflective self-cleaning coating material, which includes, by weight:

[0070] 3 parts of silicon-based mesoporous material; 5 parts of coconut oil diethanolamide; 3 parts of nano titanium dioxide; 3 parts of dodecanol methacrylate; 3 parts of polyethylene glycol type antistatic agent; 3 parts of expanded graphite; 3 parts of nano graphene; 30 parts of anhydrous ethanol; and 20 parts of acetone.

[0071] Embodiment 8

[0072] This embodiment provides a super-hydrophobic anti-reflective self-cleaning coating material, which includes, by weight:

[0073] 3 parts of silicon-based mesoporous material; 5 parts of coconut oil diethanolamide; 3 parts of nano titanium dioxide; 3 parts of dodecanol methacrylate; 3 parts of polyethylene glycol type antistatic agent; 3 parts of expanded graphite; 3 parts of nano graphene; 50 parts of anhydrous ethanol; and 30 parts of acetone.

[0074] In the present application, by using silicon-based mesoporous material as a carrier, introducing coconut oil diethanolamide active groups, and carrying nano titanium dioxide, various organic pollutants can be oxidized and decomposed, and various pollutants are washed by rainwater, thereby removing pollutants accumulated on the surface of the photovoltaic glass plate, so that the film has a self-cleaning effect; the stain resistance of the coating is improved; by adding nanographene, a velvety structure can be formed on the surface of the coating, which can reduce the reflection of the coating, increase the thermal conductivity of the coating, accelerate the decomposition and self-cleaning function of organic matter, and is conducive to absorbing light from all directions and refracting it onto the photovoltaic module, especially in a weak light environment, it is more conducive to absorbing scattered light, and the effective transmittance of sunlight can be made greater than 90%, thereby improving the permeability of the coating; by mixing a surfactant-type antistatic agent with expanded graphite, the surface of the expanded graphite is modified, and the modified expanded graphite is not easy to agglomerate, so that the expanded graphite can be evenly dispersed in the silicon-based mesopores, and will not gradually seep out of the coating during use, so that the formed coating has permanent antistatic properties, prolongs the service life of the coating, and reduces the cost of frequent replacement of the coating. Through the synergistic effect of the above components, the coating formed has good hydrophobicity, durability, stain resistance, anti-permeability and antistatic properties, which makes the coating have a good self-cleaning effect, greatly improves the service life of the coating, and reduces the cost of frequent replacement of the coating.

[0075] Table 1 Performance test results of Examples 1-8

[0076]

[0077]

[0078] According to the performance test table of Examples 1-8 in Table 1 above, it can be seen that with the increase of the content of nano-titanium dioxide, the anti-fouling effect is significantly enhanced. This is due to the photo-induced hydrophilicity of nano-titanium dioxide. Titanium dioxide can directly utilize ultraviolet light from various sources including sunlight to oxidize and decompose various organic pollutants; with the increase of the content of expanded graphite and polyethylene glycol-type antistatic agent, the durability of the coating is significantly enhanced; with the increase of the content of nano-graphene, the permeability of the coating is significantly enhanced.

[0079] Preferably, the silicon-based mesoporous material is any one or more of MCM-22, MCM-41, MCM-48 and SBA-15. For example, the silicon-based mesoporous material is a mixture of MCM-22 and MCM-41, a mixture of MCM-41 and MCM-48, a mixture of MCM-48 and SBA-15, a mixture of MCM-22 and SBA-15, a mixture of MCM-41, MCM-48 and SBA-15, and the like.

[0080] Preferably, the nano titanium dioxide is anatase phase crystal with photocatalytic function, and the particle size of the nano titanium dioxide is 2-3 nanometers. For example, the particle size can be 2 nanometers, 2.2 nanometers, 2.4 nanometers, 2.6 nanometers, 2.8 nanometers, 3 nanometers, etc. Of course, in this application, according to actual conditions and specific needs, the particle size of the nano titanium dioxide can also be other values, which is not limited here.

[0081] Preferably, in the present application, a super-hydrophobic anti-reflective self-cleaning coating material is also provided, comprising, by weight:

[0082] 1 part of silicon-based mesoporous material; 1 part of nano titanium dioxide; 1-2 parts of coconut oil diethanolamide; 1-2 parts of methacrylic acid; 1-2 parts of methacryloyloxytrimethylsilane; 1-3 parts of dodecanol methacrylate; 1-3 parts of polyethylene glycol type antistatic agent; 1-3 parts of expanded graphite; 1-3 parts of nano graphene; 30-50 parts of anhydrous ethanol; 20-30 parts of acetone.

[0083] In the present application, the coconut oil diethanolamide is 1-2 parts by weight, for example, 1 part, 1.2 parts, 1.4 parts, 1.5 parts, 1.8 parts, 2 parts, etc.

[0084] In the present application, the weight percentage of the methacryloxytrimethylsilane is 1-2 parts, for example, 1 part, 1.2 parts, 1.4 parts, 1.5 parts, 1.8 parts, 2 parts, etc.

[0085] In the present application, the weight percentage of lauryl methacrylate is 1-3 parts, for example, 1 part, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, etc.

[0086] In the present application, in addition to the direct use of ultraviolet light from various sources including sunlight by nano-titanium dioxide to oxidatively decompose various organic pollutants, methacrylic acid, methacryloyloxytrimethylsilane, and dodecanol methacrylate are introduced to react with the active groups of coconut acid diethanolamide to further enhance the stain resistance of the coating, thereby significantly improving the stain resistance of the coating.

[0087] In this application, please see Figure 1 As shown, a method for preparing a super-hydrophobic anti-reflective self-cleaning coating material is also disclosed, comprising using any of the above-mentioned super-hydrophobic self-cleaning coatings for photovoltaic solar energy, and the preparation method comprises the following steps:

[0088] S01: ultrasonically dispersing the silicon-based mesoporous material, nano-titanium dioxide, and coconut oil diethanolamide in silent ethanol, and stirring at a certain temperature to form a first mixture;

[0089] S02: adding anhydrous ethanol, polyethylene glycol type antistatic agent and expanded graphite to the first mixture and stirring evenly to form a second mixture;

[0090] S03: adding dodecanol methacrylate, nanographene and acetone to the second mixture and stirring for 30-45 minutes, mixing evenly, filtering and drying to form a self-cleaning coating material.

[0091] In the present application, by introducing the active group of coconut oil diethanolamide and reacting with nano titanium dioxide, a reaction active site is formed and deposited on the carrier of the silicon-based mesoporous material, which greatly oxidizes and decomposes various organic pollutants, and uses rainwater to wash various pollutants, thereby removing pollutants accumulated on the surface of the photovoltaic glass panel, making the film have a self-cleaning effect; improving the stain resistance of the coating;

[0092] By evenly stirring anhydrous ethanol, polyethylene glycol type antistatic agent and expanded graphite, the surface of the expanded graphite can be modified, so that the expanded graphite is not easy to agglomerate and can be evenly dispersed in the silicon-based mesopores, which greatly improves the service life of the coating and makes the coating more durable;

[0093] Finally, by adding nano-graphene and covering the mixture with silicon-based mesoporous material as the carrier with nano-graphene, the permeability of the coating is greatly improved, and the performance of the coating is greatly improved.

[0094] Further, the stirring time in step S01 is 30-45 minutes, and the stirring temperature is 80-100° C. Preferably, the stirring time in step S01 can be specifically 30 minutes, 33 minutes, 36 minutes, 38 minutes, 40 minutes, 42 minutes, 45 minutes, etc.; the stirring temperature can be specifically 80° C., 85° C., 90° C., 95° C., 100° C., etc., and can be adjusted in real time according to actual conditions and specific needs, which is not limited here.

[0095] For further information, see Figure 1 As shown, the step S03 further includes:

[0096] mixing dodecanol methacrylate, nanographene, acetone, methacryloxytrimethylsilane, and methacrylic acid to form an intermediate product;

[0097] The second mixture and the intermediate product are stirred, mixed evenly, filtered and dried to form a self-cleaning coating material.

[0098] In the present application, by adding anti-fouling materials such as methacryloxytrimethylsilane, methacrylic acid, and dodecanol methacrylate, which react with the active points of coconut oil diethanolamide and nano-titanium dioxide, the stain resistance and service performance of the coating are further greatly improved.

[0099] Furthermore, the step S01 also includes: performing a fluorination surface treatment on the silicon-based mesoporous material to introduce active reaction sites.

[0100] In the present application, by subjecting the silicon-based mesoporous material to surface fluorination treatment, on the one hand, the silicon-based mesoporous material forms a soft porous foam layer, thereby dispersing the stress of the interface layer, absorbing the impact energy, and thereby improving the toughness of the coating; on the other hand, it can undergo multi-directional covalent bonding with nano-titanium dioxide, thereby greatly enhancing the bonding strength between the silicon-based mesoporous material and nano-titanium dioxide, thereby increasing the service life of the self-cleaning coating.

[0101] Furthermore, the step S01 further includes:

[0102] The silicon-based mesoporous material with fluorinated surface treatment is placed in a polyamine acetonitrile solution for reaction for 2-3 hours. The polyamine acetonitrile solution is placed in the solution for reaction to form a soft porous foam layer. Specifically, in this embodiment, the reaction time can be 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, etc.

[0103] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A super-hydrophobic anti-reflective self-cleaning coating material, characterized in that: Ingredients by weight include: 1-3 parts of silicon-based mesoporous material; Coconut oil diethanolamide 4-5 parts; 1-3 parts of nano titanium dioxide; 3-5 parts of lauryl methacrylate; 1-3 parts of polyethylene glycol type antistatic agent; 1-3 parts of expanded graphite; 1-3 parts of nanographene; 30-50 parts of anhydrous ethanol; 20-30 parts of acetone.

2. A photovoltaic dustproof self-cleaning coating material according to claim 1, characterized in that: The silicon-based mesoporous material is any one or more of MCM-22, MCM-41, MCM-48 and SBA-15.

3. The photovoltaic dustproof self-cleaning coating material according to claim 1, characterized in that: The nano titanium dioxide is an anatase phase crystal with a photocatalytic function and a particle size of 2-3 nanometers.

4. The photovoltaic dustproof self-cleaning coating material according to claim 1, characterized in that: In parts by weight: 1 part of silicon-based mesoporous material; 1 part of nano titanium dioxide; Coconut oil diethanolamide 1-2 parts; 1-2 parts of methacrylic acid; 1-2 parts of methacryloxytrimethylsilane; 1-3 parts of lauryl methacrylate; 1-3 parts of polyethylene glycol type antistatic agent; 1-3 parts of expanded graphite; 1-3 parts of nanographene; 30-50 parts of anhydrous ethanol; 20-30 parts of acetone.

5. A method for preparing a super-hydrophobic anti-reflective self-cleaning coating material, characterized in that: The method comprises using the super hydrophobic self-cleaning coating for photovoltaic solar energy as claimed in any one of claims 1 to 4, and the preparation method thereof comprises the following steps: S01: ultrasonically dispersing the silicon-based mesoporous material, nano-titanium dioxide, and coconut oil diethanolamide in silent ethanol, and stirring at a certain temperature to form a first mixture; S02: adding anhydrous ethanol, polyethylene glycol type antistatic agent and expanded graphite to the first mixture and stirring evenly to form a second mixture; S03: adding dodecanol methacrylate, nanographene and acetone to the second mixture and stirring for 30-45 minutes, mixing evenly, filtering and drying to form a self-cleaning coating material.

6. The method for preparing a super-hydrophobic anti-reflective self-cleaning coating material according to claim 5, characterized in that: The stirring time in step S01 is 30-45 minutes, and the stirring temperature is 80-100°C.

7. The method for preparing a super-hydrophobic anti-reflective self-cleaning coating material according to claim 5, characterized in that: The step S03 further includes: mixing dodecanol methacrylate, nanographene, acetone, methacryloxytrimethylsilane, and methacrylic acid to form an intermediate product; The second mixture and the intermediate product are stirred, mixed evenly, filtered and dried to form a self-cleaning coating material.

8. The method for preparing a super-hydrophobic anti-reflective self-cleaning coating material according to claim 5, characterized in that: The step S01 further includes: The silicon-based mesoporous material is surface treated with fluorination to introduce active reaction sites.

9. The method for preparing a super-hydrophobic anti-reflective self-cleaning coating material according to claim 8, characterized in that: The step S01 further includes: The silicon-based mesoporous material with fluorinated surface treatment is placed in a polyamine acetonitrile solution for reaction for 2-3 hours.

Citation Information

Patent Citations

  • Preparation method of wear-resistant long-acting self-cleaning anti-reflecting coating, and wear-resistant long-acting self-cleaning anti-reflecting coating

    CN104071988A

  • Antistatic agent, antistatic polyamide composition, and preparation methods of antistatic agent and antistatic polyamide composition

    CN105801913A

  • Sun-screening agent microsphere completely wrapped by silicone and preparation method thereof

    CN107349113A

  • Preparation method of stain-resistant fabric

    CN114086383A

  • Photovoltaic glass self-cleaning dustproof anti-reflection nanometer material and preparation method thereof

    CN116891645A